(untitled) (Research, Society and Development, 2020)
This article had as its theme the description of Social Determinants of Health in the light of the Theory of Praxic Intervention in Nursing in Collective Health (TIPESC), aiming to report an action in a Christian community that seeks to identify and understand the contradictions of objective reality and the determinants aspects of the health-disease process found at the site and which can be systematized by TIPESC. It is a descriptive study with a quantitative approach, an experience report type, carried out through the observation of a Christian community, taking into account the concept of the health-disease process and the dimensional category used by the theory, in its first stage, to capture objective reality. During the visit the community was able to observe and interpret the reality of these individuals, confirming what establishes the theory that understands the importance of social determinants in the well-being of individuals. Thus, it was found that the interviewees had a reality which provided a lower quality of life. Due to the mentioned facts, the analysis of the descriptive aspects about the variables that influence the health-disease process, it was possible to consolidate the understanding regarding the importance of the systematization of nursing care in public health, as well as to obtain a broader view about it collective health and the understanding of the dynamics in which nursing care occurs in practice, both individually and collectively.